Cone beam computed tomography in Endodontics – a review. (2nd April 2014) - Patel, S.; Durack, C.; Abella, F.; Shemesh, H.; Roig, M.; Lemberg, K.
Abstract Cone beam computed tomography (CBCT) produces undistorted three‐dimensional information of the maxillofacial skeleton, including the teeth and their surrounding tissues with a lower effective radiation dose than computed tomography. The aim of this paper is to: (i) review the current literature on the applications and limitations of CBCT; (ii) make recommendations for the use of CBCT in Endodontics; (iii) highlight areas of further research of CBCT in Endodontics.